Monitoring Small-Pelagic Fishery Utilization in Java Sea Based on Fishing Log Book - Patmiarsih, Sri; Juniar, Rista Devi; Efendi, Diding Sudira (Politeknik Ahli Usaha Perikanan, 2023)
The most attention issue of sustainable fisheries management is related to the availability of catch and fishing efforts data with the spatio-temporal distribution. The monitoring data plays important to evaluate the fish stock status and fishery dynamic in the waters. As dependent-fishery data, logbook data is a reliable data source for estimating the utilization rate of fish resources and designing effective regulation tools in fisheries management areas. This study aims to analyze catch composition, spatial and temporal distribution, and productivity (catch per unit effort) of small-pelagic purse seine fisheries in the Java Sea using fishing logbook data. The result shows the highest It was found that the catch composition of small pelagic purse seines was dominated by longtail tuna/kawa-kawa, scad (Decapterus spp.), and sardinella fimbriata with the highest catches annually occurring in September 2021, March 2020, and November 2019. However, the highest productivity was achieved in September 2021, May 2020 and June 2019, namely 1,290 kg/setting/day, 1,700 kg/setting/day, and 1,660 kg/setting/day, respectively. Regarding spatial distribution, the highest productivity was in the northern and central parts of the Java Sea and the southern parts of Kalimantan.